Avaliação exploratória da eficiência econômica em sistemas de manufatura - Antunes, Tiago dos Santos (Universidade do Vale do Rio dos Sinos, 2020)
The increase in productivity and efficiency in manufacturing systems has attracted growing interest from academia and companies. An alternative to analyzes carried out using traditional technical measures such as Overall Equipment Effectiveness (OEE) is the analysis of Economic Efficiency using Data Envelopment Analysis (DEA). Despite the high amount of research on the analysis of Economic Efficiency with DEA, empirical evidence is scarce in the literature, especially in manufacturing systems. Therefore, it is relevant to evaluate the results of Economic Efficiency to contribute to the improvement of the result as a whole of the company in relation to Technical Efficiency in a manufacturing system. This research analyzes the results of Economic Efficiency, Technical Efficiency and Allocative Efficiency in a company in the Brazilian footwear sector. The calculated efficiencies were evaluated longitudinally over a period that covers the months of January 2017 to June 2019 for the types of women's and sports shoes, represented in four models (A, B, C, and D), combining the Data Envelopment Analysis (DEA) and the Wilcoxon test in a case study. As a result, it is evident that Economic Efficiency, Technical Efficiency, and Allocative Efficiency present significant differences in the result of the efficiency of the evaluated models. Finally, the research shows which types of efficiency contribute to evaluating the manufacturing system and the financial result of the investigated company.
Keywords: Eficiência econômica (EE); Eficiência técnica (ET); Eficiência alocativa (EA); Análise envoltória de dados (DEA); Sistema de manufatura; Economic efficiency (EE); Technical efficiency (TE); Allocative efficiency (AE); Data envelopment analysis (DEA); Manufacturing system; ACCNPQ::Engenharias::Engenharia de Produção